Conservative analysis of Synaptopodin‐2 intron sense‐overlapping lncRNA reveals its novel function in promoting muscle atrophy. Issue 4 (19th May 2022) - Jin, Jianjun; Du, Mengmeng; Wang, Jian; Guo, Yubo; Zhang, Jiali; Zuo, Hao; Hou, Yunqing; Wang, Shanshan; Lv, Wei; Bai, Wei; Wang, Jin; Zhan, Xizhen; et al.
Abstract: Background: Dissection of the regulatory pathways that control skeletal muscle development and atrophy is important for the treatment of muscle wasting. Long noncoding RNA (lncRNA) play important roles in various stages of muscle development. We previously reported that Synaptopodin‐2 ( SYNPO2 ) intron sense‐overlapping lncRNA ( SYISL ) regulates myogenesis through an interaction with enhancer of zeste homologue 2 (EZH2). However, it remains unclear whether SYISL homologues exist in humans and pigs, and whether the functions and mechanisms of these homologues are conserved among species. Methods: Bioinformatics, cell fractionation, and quantitative real‐time polymerase chain reaction (qRT‐PCR) analyses were used for the identification and molecular characterization of SYISL homologues in humans and pigs. Effects on myogenesis and muscle atrophy were determined via loss‐of‐function or gain‐of‐function experiments using C2C12 myoblasts, myogenic progenitor cells, dexamethasone (DEX), and aging‐induced muscle atrophy models. RNA pulldown, RNA immunoprecipitation, dual luciferase reporting, and co‐transfection experiments were used to explore the mechanisms of SYISL interactions with proteins and miRNAs. Results: We identified SYISL homologues in humans (designated hSYISL ) and pigs (designated pSYISL ). Functional experiments demonstrated that hSYISL and pSYISL regulate myogenesis through interactions with EZH2. Interestingly, we showed that SYISL functions to regulate muscle atrophy and sarcopenia through comparative analysis. SYISL is significantly up‐regulated after muscle atrophy ( P < 0.01); it significantly promotes muscle atrophy in DEX‐induced muscle atrophy models ( P < 0.01). SYISL knockdown or knockout alleviates muscle atrophy and sarcopenia in DEX‐induced and aged mice. The tibialis anterior (TA) muscle weight of 3‐month‐old wild‐type (WT) mice decreased by 33.24% after DEX treatment ( P < 0.001), while the muscle weight loss of 3‐month‐old SYISL knockout mice was only 18.20% after DEX treatment ( P < 0.001). SYISL knockout in 18‐month‐old WT mice significantly increased the weights of quadriceps (Qu), gastrocnemius (Gas), and TA muscles by 10.45% ( P < 0.05), 13.95% ( P < 0.01), and 24.82% ( P < 0.05), respectively. Mechanistically, SYISL increases the expression levels of the muscle atrophy genes forkhead box protein O3a ( FoxO3a ), muscle ring finger 1 ( MuRF1 ), and muscle atrophy‐related F‐box ( Atrogin‐1 ) via sponging of miR‐23a‐3p/miR‐103‐3p/miR‐205‐5p and thus promotes muscle atrophy. Additionally, we verified that human SYISL overexpression in muscles of 18‐month‐old WT mice significantly decreased the weights of Gas, Qu, and TA muscles by 7.76% ( P < 0.01), 12.26% ( P < 0.05), and 13.44% ( P < 0.01), respectively, and accelerates muscle atrophy through conserved mechanisms. Conclusions: Our results identify SYISL as a conserved lncRNA that modulates myogenesis in mice, pigs, and humans. We also demonstrated its previously unknown ability to promote muscle atrophy.